Persistent radical anions in panchromatic D-A hybrid heterostructures induced by anion-π interactions. (September 2020) - You, Ming-Hua; Di, Yi-Ming; Li, Meng-Hua; Li, Hao-Hong; Lin, Mei-Jin
Abstract: The combination of N, N ′-dipyridyl-tetrachloroperylene diimide (4Cl-DPPDI) buliding blocks with lead iodides in the presence of hydrogen iodides led to a novel D-A hybrid heterostructure with segregated iodoplumbate anions and 2-D H-bonded 4Cl-DPPDI networks as electron donors and acceptors. Due to the compact anion-π interactions as well as small energy gaps between the donors and acceptors, persistent and stable radical anions are generated in such a unique complex triggered by natural-light irradiation, which thus exhibits a panchromatic absorption. Graphical abstract: Induced by the compact anion-π interactions and small energy gaps between the donor and acceptor components, persistent radical anions are photogenerated in a novel D-A hybrid heterostructure, which thus exhibits a panchromatic absorption. Image 1 Highlights: A novel D-A hybrid heterostructure composed of perylene diimide dyes and iodoplumbate anions have been synthesized. In the structure, the iodoplumbate anions and perylene diimide networks acted as electron donors and acceptors, respectively. The donor and acceptor components in the heterostructure are interconnected through the anion-π interactions. Due to the compact connections, persistent and stable radical anions are triggered by natural-light irradiation. The generation mechanism of these persistent and stable radical anions was studied through theoretical calculation.